2020
DOI: 10.1088/1742-6596/1440/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Application of problem based learning model to improve problem solving ability of student of XI science grade in chemistry

Abstract: The purpose of this study was to determine the effect of the application of problem-based learning models compared to conventional learning models to improve students’ problem solving skills in XI IPA SMAN 2 Labuapi This research is quasi-experimental, which used nonequivalent control group design. The population in this study were all students of XI IPAN SMAN 2 Labuapi in the academic year 2015/2016. The research sample consisted of two classes, namely class XI IPA 1 as an experimental class and class XI IPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
1
6
0
1
Order By: Relevance
“…When the teachers successfully encourage and cultivate a culture of learning through problem-solving, it fosters the development of various skills, as highlighted by this study. The findings of this study are consistent with previous studies that emphasised the important role of PBL in improving critical thinking abilities (Gholami et al, 2016;Lapuz & Fulgencio, 2020;Oja, 2011;Tiwari, Lai, So, & Yuen, 2006), teamwork (Adnan et al, 2009;Deep et al, 2019), team-based problem-solving skills (Helmi et al, 2016), problem-solving skills (Kadir et al, 2016;Kurniawan & Sofyan, 2020;Sari, 2021;Simamora et al, 2017), and communication skills (Deep et al, 2019;Salari et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When the teachers successfully encourage and cultivate a culture of learning through problem-solving, it fosters the development of various skills, as highlighted by this study. The findings of this study are consistent with previous studies that emphasised the important role of PBL in improving critical thinking abilities (Gholami et al, 2016;Lapuz & Fulgencio, 2020;Oja, 2011;Tiwari, Lai, So, & Yuen, 2006), teamwork (Adnan et al, 2009;Deep et al, 2019), team-based problem-solving skills (Helmi et al, 2016), problem-solving skills (Kadir et al, 2016;Kurniawan & Sofyan, 2020;Sari, 2021;Simamora et al, 2017), and communication skills (Deep et al, 2019;Salari et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In the context of higher learning education, PBL has been broadly accepted as one of the teaching approaches to improve students' skills and, thus, enhancing graduates' employability (Jabarullah & Hussain, 2019;Okolie et al, 2020). Among others, previous research found that PBL could improve students' learning motivation (Moskovsky et al, 2013), lateral thinking abilities (Mustofa & Hidayah, 2020), critical thinking abilities (Gholami et al, 2016;Oja, 2011;Tiwari et al, 2006), teamwork (Adnan et al, 2009), team-based problem-solving skills (Helmi, Mohd-Yusof, & Phang, 2016), problem-solving skills (Kadir et al, 2016;Kurniawan & Sofyan, 2020;Simamora et al, 2017), and critical thinking skills (Asyari et al, 2016;Gholami, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[41] The problems that are presented in learning with problem-based learning model are problems related to everyday life so that problem-based learning model is suitable to be applied to physics learning. The use of a problem-based learning approach in teaching physics can help maintain the success of teachers to carry out an in-depth approach to learning activities and improve attitudes towards physics [42].…”
Section: Table 1 Descriptive Statistics On Student Responses To Probmentioning
confidence: 99%
“…Peserta didik dilatih agar mampu bekerja sama dengan anggota kelompoknya masing-masing dalam memunculkan ide, saling bertukar ide dan akhirnya memilih ide yang sesuai dengan solusi yang diinginkan. Keterampilan memecahkan masalah harus dilatih dan dikembangkan sejak dini agar peserta didik mampu memecahkan masalah kontekstual melalui materi yang diajarkan (Kurniawan & Sofyan, 2020). Proses pemecahan masalah yang terdapat pada model PBL membutuhkan sikap percaya diri untuk menentukan langkah-langkah dalam menyelesaikan masalah.…”
Section: Pendahuluanunclassified